Computed tomographic findings in lymphomas of the head and neck at King Chulalongkorn Memorial Hospital - Kittyon, Navaporn; Lerdlum, Sukalaya (Chulalongkorn Medical Journal, 2023)
Background : Lymphoma is the second most common neoplasm in the head and neck. According to the recent study in Thailand, the incidence of malignant lymphoma was increasing. The roles of CT were assessment of known tumor, identification of occult tumor sites, assessment of treatment response, and recurrent tumor diagnosis. Objective : To describe and characterize CT findings of lymphoma of head and neck of Patients at King Chulalongkorn Memorial Hospital (KCMH). Design : Retrospective descriptive study Setting : Department of Radiology, King Chulalongkorn Memorial Hospital (KCMH) Materials and Methods : We retrospectively reviewed nodal and extranodal findings on baseline CT scan of 62 patients, who were newly diagnosed with lymphoma of the head and neck by tissue pathology and underwent pretreatment CT scan of the neck, orbit or paranasal sinuses in KCMH from January 1, 2006 to October 31, 2011. Results : Three patients had Hodgkin lymphoma (HL) and 59 Non-Hodgkin lymphomas (NHL). Forty six patients (74%) had primary lymphoma of the head and neck. The other 16 patients (26%) had systemic lymphoma that partly involved the head and neck. CT manifestations in lymphoma of the head and neck varied; 24% were isolated nodal disease (type I CT pattern); 15% were isolated extranodal lymphatic/extralymphatic disease (type II CT pattern); 56% were combined nodal and extranodal lymphatic/ extralymphatic diseases (type III CT pattern); and, 5% were multifocal extranodal lymphatic/extralymphatic diseases (type IV CT pattern). Sites of extranodal involvement found in this study were at Waldeyer’s ring (39%), orbital (32%), nasal cavities (13%), mandible (2%) and thyroid gland (2%). About 16% of the patients had bone destruction. Conclusions : There were variable CT manifestations of lymphoma, from nodal to extranodal lymphatic to extranodal extra-lymphatic disease. NHL is much more common than HL and frequently presents with combined nodal and extranodal diseases (either lymphatic or extralymphatic diseases). Frequently extranodal sites in this study are Waldeyer’s ring, orbital and sinonasal cavities in descending order of frequency. There is HIV-associated lymphoma, such as plasmablastic lymphoma of the mandible, that has unusual presence in patients with normal immune status.